Creating A Nationwide Nonpartisan Initiative for Family Caregivers in Political Party Platforms. Issue 6 (10th March 2017) - Scribner, Ben; Lynn, Joanne; Walker, Victoria; Morgan, Les; Montgomery, Anne; Blair, Elizabeth; Baird, Davis; Goldschmidt, Barbara; Kirschenbaum, Naomi
Abstract : Policymakers have been slow to support family caregivers, and political agendas mostly fail to address the cost burdens, impact on employment and productivity, and other challenges in taking on long‐term care tasks. This project set out to raise policymakers' awareness of family caregivers through proposals to Republican and Democratic party platforms during the 2016 political season. The Family Caregiver Platform Project (FCPP) reviewed the state party platform submission process for Democratic and Republican parties in all 50 states and the District of Columbia. We built a website to make each process understandable by caregiver advocates. We designed model submissions to help volunteers tailor a proposal and recruited caregiver advocates participating in their state process. Finally, we mobilized a ground operation in many states and followed the progress of submissions in each state, as well as the formation of the national platforms. In 39 states, at least one party, Republican or Democrat, hosted a state party platform process. As of September 2016 FCPP volunteers submitted proposals to 29 state parties in 22 states. Family caregiver language was added to eight state party platforms, one state party resolution, two bipartisan legislative resolutions, and one national party platform. The FCPP generated a non‐partisan grassroots effort to educate and motivate policymakers to address caregiving issues and solutions. Democratic party leaders provided more opportunities to connect with political leaders, with seven Democratic parties and one Republican party, addressing family caregiver issues in their party platforms.